Epidemiology of injuries and illnesses in elite wheelchair basketball players over a whole season - a prospective cohort study - Weith, M.; Junge, A.; Rolvien, T.; Kluge, S.; Hollander, K. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Background Wheelchair basketball is an adaptation of pedestrian basketball and one of the most popular Paralympic sports worldwide. The epidemiology of health problems in wheelchair basketball has been prospectively studied only during the Paralympic Games, the 2018 World Championships, the 2021 South America Wheelchair Basketball Championship, and one season of two American intercollegiate wheelchair basketball teams. The objective of the study was to prospectively monitor and analyze the prevalence, incidence, burden, and characteristics of injuries and illnesses in a wheelchair basketball league during an entire season for the first time.